Synthesis of sulfamic acid supported on Cr-MIL-101 as a heterogeneous acid catalyst and efficient adsorbent for methyl orange dye. Issue 37 (5th June 2018) - El-Hakam, Sohier A.; Samra, Salem E.; El-Dafrawy, Shady M.; Ibrahim, Amr A.; Salama, Reda S.; Ahmed, Awad I.
Abstract : Sulfamic acid was incorporated into MIL-101 (Cr). The samples exhibited excellent adsorption performance for MO dye and acted as heterogeneous catalysts for coumarin and xanthene synthesis. Abstract : Typical highly porous metal–organic framework (MOFs) materials based on chromium benzenedicarboxylates (Cr-BDC) were prepared through a one-pot hydrothermal synthesis, and were then modified by loading the appropriate ratio of sulfamic acid (SA) using a simple impregnation technique. Pure and modified MIL-101 was characterized by XRD, TEM, SEM and FT-IR measurements. TEM and SEM measurements confirmed that the MIL-101 particles preserved their regular octahedral structure after loading with different weight contents of sulfamic acid. The total number of acid sites and Brønsted to Lewis acid sites ratio (B/L) were examined using potentiometric titration and pyridine adsorption. The acid strength and surface acidity of SA/MIL-101 gradually increased after the modification of Cr-MIL-101 by sulfamic acid crystals up to 55 wt%, then decreased again. The catalytic performance of the solid catalysts was confirmed in the synthesis of 14-phenyl-14 H -dibenzo [ a, j ] xanthene and 7-hydroxy-4-methyl coumarin. In the two reactions, the sample with 55% sulfamic acid loaded on MIL-101 displayed the highest catalytic activity and acidity. The adsorption behaviors of sulfamic acid loaded on MIL-101 materials for methyl orange (MO) as an anionic dye were studied, and were exceptionally suitable for the Langmuir adsorption isotherm. All loaded adsorbents showed high adsorption capacity for methyl orange at 25 °C. The results indicate that the adsorption capacity was modified by changing the amount of sulfamic acid loaded on MIL-101.